Physiological responses of callus from gerbera jamesonii Bolus ex. Hook f. to Gamma Irradiation - Hasbullah, N.A.; Taha, R.M.; Saleh, A.; Mohamed, N. (2012)
In the present study, in vitro mutagenesis techniques were applied to investigate the effects of gamma irradiation at 0, 10, 20, 30, 40, 50 and 60 Gy on physiological changes in callus of Gerbera jamesonii Bolus ex. Hook f. Biochemical changes in chlorophyll and soluble protein content of pre- and post- irradiated Gerbera callus were studied. Non-irradiated callus demonstrated the highest amount of chlorophyll content as compared to callus irradiated at 10, 20, 30, 40, 50 and 60 Gy. In addition, the amount of chlorophyll b was relatively higher than chlorophyll a in both the irradiated and non-irradiated callus, except for callus irradiated at 10 Gy. Biochemical differentiation based on total soluble protein content revealed gradual reduction after day 9 of exposure to gamma irradiation. Reduction of soluble protein content was observed in all the treatments as the increase of incubation period.